Cytological and Molecular Approaches for Ploidy Determination: Results from a Wild Walleye Population. (11th May 2022) - Farrell, Collin J.; Johnson, Brett M.; Hansen, Adam G.; Myrick, Christopher A.; Anderson, Eric C.; Delomas, Thomas A.; Schreier, Andrea D.; Van Eenennaam, Joel P.
Abstract: With the increasing use of triploid fish for sport fisheries management, biologists, researchers, and managers working in field environments need practical methods to determine ploidy. Cytological methods (e.g., flow cytometry, Coulter counter) using erythrocytes are the most common for ploidy determination in fishes. However, collecting and storing erythrocytes can be logistically challenging during field work, and donor fish need to be alive or freshly killed. With rapid advances in molecular genetics, biologists, researchers, and managers may be unaware of molecular approaches for ploidy determination that could alleviate the difficulties associated with cytological methods and allow ploidy determination from archived samples (e.g., fin clips, scales, otoliths). In this study, we analyzed the agreement between molecular‐based (using fin tissue) and Coulter counter‐based (using blood) ploidy determinations for Walleyes Stizostedion vitreum —the first assessment of concordance between molecular and cytological methods for determining ploidy in the family Percidae. We found that agreement between these two methods was >98%. The high degree of agreement and greater ease of collecting and storing samples for molecular‐based approaches relative to the traditional cytological ones support the utility of molecular methods for ploidy determination.